Education and Training for the Fourth Industrial Revolution - Georg Spoettl; Vidmantas Tūtlys (Faculty of Engineering, Universitas Negeri Yogyakarta, 2020)
Within the context of the 4th Industrial Revolution as an overall paradigm change, organization and work processes must switch together with automation following and real-time control. This applies to the contents of labor and to the interaction and connection between human and technology. Up to this point, there are only a few empirical studies about how digitized, decentralized and closely connected production system with